The Albeşti Limestone: a geoheritage and cultural heritage in Romania - Viorel Ilinca; Viorica Milu; Sorina Peligrad; Ion Gheuca (Journal of Maps, 2023)
ABSTRACTThe paper explores and documents the Eocene limestones from the Albeşti village (Argeş County, Romania) in terms of the relationship between geology, geoheritage and cultural heritage. Known as the Albeşti Limestone/Stone, this rock, extracted from small quarries, has been used for centuries in the construction of an impressive number of public buildings, monuments, houses, etc. Nowadays, many of them are on the List of the Historical Monuments of Romania; one is a designated UNESCO World Heritage Site (Horezu Monastery, Vâlcea County). The findings of this research are synthesized and presented in several maps resulted from integration of published and unpublished data with our field survey. The study emphasis the Albeşti Limestone both as an important geoheritage (the Albeşti Nummulitic Limestone Nature Reserve, established in 1954) and a significant heritage stone of national interest that could have a substantial role in heritage preservation, geoeducation, and geotourism development.